A survey of malaria vectors feeding preference, biting site and resting behaviour in the malaria elimination settings of Dembiya District, north-western Ethiopia - Mihretu Tarekegn; Sisay Dugassa; Yohannes Negash; Habte Tekie; Yitbarek Woldehawariat (Malaria Journal)
Abstract Background Despite the progress in scaling vector control interventions in Ethiopia, malaria is still a major health problem in the country. Monitoring of the local vector populations and the effectiveness of vector control strategies is necessary to guide programme decisions to optimize malaria prevention efforts. This study investigated the feeding preference, the biting behaviour and resting behaviours of Anopheles mosquitoes in selected localities of Dembiya District. Methods Adult Anopheles mosquitoes were sampled indoors and outdoors from June 2018 to May 2019 using CDC light traps, pyrethrum spray catches, artificial pit shelters, and mouth aspirators at both Guramba Bata and Arebiya study sites. Anopheles mosquitoes were identified to the species level. Their blood meal source and Plasmodium sporozoite infections were determined using an enzyme-linked immunosorbent assay. Results Anopheles mosquitoes belonging to 11 species were identified from 2,055 collected mosquito specimens. Anopheles pharoensis was the predominant species at both the Guramba Bata (46.5%) and Arebiya (46.2%) study sites. The CDC light traps caught the highest number of Anopheles mosquitoes in both study sites. In Guramba Bata the density of outdoor host-seeking and resting Anopheles mosquitoes were higher than indoors (P ≤ 0.05). The human blood indexes (HBI) of indoor and outdoor host-seeking Anopheles arabiensis were 17.4% and 15.3%, respectively. The entomological inoculation rate (EIR) of outdoor host-seeking An. arabiensis was 4.7 infective bites/person/year. Additionally, the outdoor EIR of host-seeking Anopheles coustani was 25.7ib/p/year. Conclusions Anopheles mosquitoes in Dembiya district were more likely to seek a host and rest outdoors than indoors. A reevaluation of vector control strategies is needed to ensure Ethiopia remains on the path to malaria elimination. The detection of Plasmodium circumsporozoite protein in potential secondary vectors, such as An. coustani requires further investigation to substantiate their role in malaria transmission.